Marketing: An Introduction - Gary Armstrong, Philip T. Kotler (Upper Saddle River, NJ Pearson Prentice Hall, 2011)
How do we get you moving? By placing you-the customer-in the driver's seat. Marketing introduces the leading marketing thinking on how customer value is the driving force behind every marketing strategy.
Age Group: Adult
Includes bibliographical references (p. R1-R23) and indexes.
Keywords: Business; Marketing; Academic; Textbooks; Management